The Role of Reading Habits in Shaping Writing Skills among Students - Hidayat, Agus (Journal of Linguistics and Social Sciences, 2025)
This study looks at how reading habits help students improve their writing skills. It seeks to explain how reading and writing are connected. This study looks at a number of publications to understand how reading helps people write better. It uses a method that focuses on collecting information from different sources like journals and online databases. Important results show that reading often helps to make vocabulary, grammar, and writing better. Many kinds of reading materials, like school books, stories, and online content, help improve writing quality in different ways. Also, good reading skills are very important for writing well. But, problems like digital distractions and bad feelings about reading make it hard for students to build good reading habits. This can also affect their writing skills. These findings show that it is very important to build good reading habits to improve writing skills. This means we need to have teaching methods that help students with both reading and writing together. There are ideas for students, teachers, and people who make school plans. Also, there are tips for future studies to help with missing information in the books